Risk Factors and Patterns of Drug‐Drug Interactions in Two Categories of Level‐3 Hospitals in Dhaka: A Cross‐Sectional Study - Md. Abdus Samadd; Farhan Tanvir Patwary; Md Momin Islam; Ashfia Tasnim Munia; K. M. Yasif Kayes Sikdar; Md. Raihan Sarkar (Health Science Reports)
ABSTRACT Background and Aims Drug‐drug interactions (DDIs) are a significant health issue that may adversely affect the health and well‐being of patients. This study assesses and compares potential DDI (pDDI) patterns, severity, and associated risk factors in government and private hospitals in Dhaka, Bangladesh. Methods A total of 188 and 206 prescriptions were collected from various government and private hospitals' outdoor departments, respectively, by capturing pictures of the prescriptions. Bivariate analyses were performed through STATA 15. MedScape drug interaction checker was applied to identify pDDIs, while their consequences were obtained from DrugBank and MedScape. Results Private hospitals had more pDDIs containing prescriptions than government hospitals (62.62% and 57.97%, respectively). The mean pDDIs cases were 3.29 in the private hospitals, while at government hospitals they were 3.02. Among the detected pDDIs, pharmacodynamic pDDIs were predominat, accounting for 63.32% and 66.23% of total events in government and private hospitals, respectively. Severity‐wise, both types of hospitals had almost equal amounts of serious (10.34% vs. 9.18%), moderate (68.96% vs. 59.61%), and minor (20.06% vs. 21.79%) pDDIs. Polypharmacy was crucial in pDDI cases, responsible for 70.21% and 81.83% of pDDIs in government and private hospitals, respectively. Multiple comorbidities with pDDIs were more common in private hospitals (24.46% vs. 18.93%), while government hospitals displayed a higher frequency of pDDIs with one comorbidity (24.75% vs. 17.55%). Non‐mention of comorbidities was correlated with both types of hospitals (p ≤ 0.01) in pDDIs cases. Furthermore, considerable amounts of pDDIs in prescription error categories were detected. Both types of hospitals had a prevalence of antihypertensive, antidiabetic, psychotic, and antiplatelet‐related pDDIs. Conclusion The two kinds of hospitals exhibited similar pDDI patterns, while their associations were random with the risk variables. When prescribing pharmacokinetics and pharmacodynamics pDDIs, physicians should evaluate the risk‐benefit ratio.